Case report: Surgical treatment of pyloric obstruction with intramural gastric abscess induced by fragmented crystalline foreign materials in a dog - Kim, Jihun; Son, Hyunglak; Lee, Sungin (Frontiers in Veterinary Science, 2024)
An 11-year-old neutered male Maltese presented with a 2-day history of persistent vomiting and lethargy. Abdominal ultrasonography revealed a hypoechoic marginal mass with gastric wall thickening in the pyloric region of the stomach. Computed tomography revealed a non-contrastenhanced mass in the pyloric antrum causing pyloric outflow obstruction. Imaging studies suggested a tumor and surgical treatment was performed due to the deterioration of the patient's condition. The pyloric mass was excised, and the stomach and duodenum were anastomosed via pylorectomy and gastroduodenostomy (Billroth I procedure). Postoperatively, the pyloric outflow obstruction resolved, clinical symptoms improved, and no significant complications were observed. Histopathological examination revealed a gastric abscess characterized by a mass-like area with abundant necrosis. Angular fragmented crystalline foreign materials were observed within the lesion. To our knowledge, this is the first reported case of an intramural gastric abscess caused by fragmented crystalline foreign materials in a dog. Although rare, this case highlights the importance of considering gastric abscesses in the differential diagnoses of gastric masses. If the cause of the gastric abscess is an invisible foreign material, postoperative follow-up should be considered to monitor for potential recurrence.